Hybrid approach for designing smart adaptive Web Sites - Kelash, Hamdey M. (2009)
The very beginning of the research on Smart Adaptive Web Systems (SAWS). They are systems that adapt their response based on the context in which they are used. In AWS, three main sources of information have been identified are: user, environment, and technology. To design a site for adaptivity, the site s parts must be changeable according to users needs and interests. This paper represents a careful study of a large number of adaptive web systems which are used for adapting predesigned web pages and automatic synthesizing web pages. It suggests a new approach to extract the user s interest without the need of many visits to the web site or viewing the catalog in details. Different E-metrics are measured to evaluate the user s history, extract users interests, create adaptable interface, and synthesize a new page with special features referring to users needs and interests and also predict the next step the user may need.